Glaciomarine turbidite and current controlled deposits in Prydz Bay, Antarctica - Kuvaas, Berit; Leitchenkov, German (Marine Geology, 1992)
A thick sequence (up to 2200 m) of presumed post late Eocene/early Oligocene glaciomarine sediments is inferred to be present on the Prydz Bay continental rise. In the absence of information from drillholes, we correlate to ODP Leg 119 drillsites on the shelf and compare with the seismic reflection pattern of glaciomarine sequences in the Weddell Sea. The inferred glaciomarine sediments in Prydz Bay appear to be deposited in a complex manner, suggesting interaction by both turbidity cur rents and strong bottom currents. Reflection seismic profiles from the lower continental slope and rise shows an abundance of current influenced deposits, such as sediment waves and large sediment ridges with similarities to contourite drifts. In addition, large channel-levee complexes are abundant, suggesting deposition by turbidity currents and other massflow processes. Large channels and sediment ridges trend oblique to the continental margin. The geometry and character of the seismic reflection pattern suggest that the ridges have been deposited under the combined influence of overflow from downslope channelized turbidity currents and strong bottom water flow. The observed sediment waves and the difference along eastern and western channel margins suggest that bottom currents are flowing towards the west. We suggest that the initiation of turbidite sedimentation occurred in the late Eocene-early Oligocene, when the Amery Ice Shelf reached the shelf edge for the first time. Onset of current controlled deposition may possibly be related to the opening of the Drake Passage at the Oligocene/Miocene boundary.
Keywords: Sørishavet; Weddellhavet; havbunnen; kontinentalmargin; marin geologi

The Crary Fan: A trough-mouth fan on the Weddell Sea continental margin, Antarctica - Kuvaas, Berit; Kristoffersen, Yngve (Marine Geology, 1991)
Multichannel seismic investigations show the presence of a large trough-mouth fan deposit on the continental margin in the southern Weddell Sea. A characteristic feature of the fan is relatively few, but large canyons and/or channels which appear to have been stable for long periods. Levees associated with the channels may reach thicknesses of more than 1 km. Drilling during ODP Leg 113 recorded the presence of glaciers in East Antarctica since early Oligocene time, and the seismic stratigraphic evidence suggests that the submarine fan is largely composed of glacigenic sediments. The channel-levee systems and complexes indicate several growth phases, apparently controlled by glacial/interglacial climate fluctuations, with maximum fan growth during glacial periods. The present interglacial period is characterized by strong and erosive flow of Ice Shelf Water running down the western slope of the fan and carrying only minor amounts of suspended matter. The fan is essentially sediment starved during interglacial periods. The dimensions of the channel-levee complexes and the persistent loci of sediment supply suggest that turbidite sedimentation resulted from melting of wet-based glaciers at or near the shelf edge, which has consequently prograded 70-80 km seaward.
Keywords: Sørishavet; Weddellhavet; havbunnen; isshelf; kontinentalmargin; kontinentalsokkel; marin geologi; seismologi